Postcolonialism and Christian Theological Reasoning: the Trap of Re-colonialization - Awad, Najib George (Exchange, 2026)
This essay looks at the impacts of postcolonial reasoning on Christian theology today. It focuses on the influence of some trends of Postcolonialism on some forms of reasoning in contemporary Christian theology to discern both the valuable and the problematic ramifications on the understanding of theology that such trends of postcolonializing orientations leave in relation specifically to the notion of ‘binarism’ and its traces in some relevant theological views. In the postcolonial realm of reasoning, there are scholars who claim that binarism is one of the surviving debris of colonialism, and they explain that postcolonialization means exposing binarism to serious transformation. The essay would demonstrate that, in its sustained reliance on binarity, there are trends of postcolonial theology that are still lingering within the zone of coloniality, or, one might say, floating within a nebulous sphere of pseudo-postcoloniality. By focusing on three particular concentrations in the studied postcolonial theologization circles of reasoning today, the essay demonstrates that the postcolonial theologians who endorse these orientations neither hybridized binarism to lessen its impact, nor do they subalternize and displace it to liberate the circle of theologization from it. They, rather, opt for mimicking this colonial binarism in their very postcolonial attempt at ridding theology from it. They did this by binarizing ‘hybridity’ instead of hybridizing binarity.